Exposure to house dust endotoxin and allergic sensitization in allergic and nonallergic children living in Adana, Turkey - Yılmaz, Mustafa; Altıntaş, Derya Ufuk; Bingöl-Karakoç, Gülbin; İnal, Ayfer; Kılıç, Mehmet; Sütolukta, Zeynel; Güneşer-Kendirli, Seval (The Turkish Journal of Pediatrics, 2009)
It has been suggested that exposure to elevated levels of endotoxin decreases the risk of allergic sensitization. The objective of our study was to analyze associations between house dust endotoxin levels and allergic sensitization in children. One hundred children with self-reported allergic diseases and 100 healthy children were randomly selected from a list of a previous prevalence study in school children. These children attended the study center again to complete a detailed questionnaire and medical examination including skin prick test and pulmonary function test. Of these children, 65 had allergen sensitization. Parents of a total 100 children (50 allergic and 50 healthy) agreed to house dust sampling in their homes. Thirty-five allergic children had asthma and 25 had rhinitis. Thirteen allergic and 14 healthy children lived in rural areas. The endotoxin content was quantified using a chromogenic kinetic Limulus amoebocyte lysate test. Endotoxin was at a detectable level in all dust samples. Endotoxin levels ranged from 0.05 to 309 EU/ml, with a geometric mean of 61.8 (confidence interval [CI] %) (50-73) EU/ml. There were no differences in house dust endotoxin levels between allergic and nonallergic children (p=0.153). On the whole, the mean level of endotoxin in rural homes was higher than that of urban homes, but this was not statistically significant (p=0.354). The highest endotoxin level was found in the homes of nonallergic children living in the rural areas and the lowest level in the homes of allergic children living in an urban area; however, this was not important statistically (p=0.320). Exposure to endotoxin was not associated with a risk of allergic sensitization (odds ratio [OR]=0.98; 95% CI: 0.91-1.05, p=0.609). In conclusion, supposing that the current level of endotoxin may reflect that in the past, the levels of endotoxin in living room floor dust of homes of allergic and nonallergic children in our study population were not associated with allergic sensitization. Further studies are needed on this topic.